KONTRIBUSI PELATIHAN HIJAU, PENERIMAAN DAN SELEKSI KARYAWAN HIJAU, DAN PEMBERDAYAAN HIJAU DALAM MENINGKATKAN KINERJA MANAJEMEN HIJAU - Gabriel Rudra Renata; Achmad Choerudin Choerudin (Jurnal Perilaku dan Strategi Bisnis, 2025)
This study aims to analyze the effect of Green Training, Green Recruitment and Selection, and Green Empowerment on Green Performance Management at the Ahass Motorcycle Repair Shop, Bantul. This research was conducted through a quantitative approach. Primary data collection is distributing questionnaires to 214 respondents with a sampling technique using double sampling. The analysis tool is the validity test along with the Smart program reliability test (PLS) version 4.0, with Variance Based Structural Equation Modeling (SEM) as the basis of the approach. The results of the study show that if Green Training has a positive and significant effect on Green Performance Management, Green Recruitment and Selection has a positive and significant effect on Green Performance Management, and Green Empowerment has a positive and significant effect on Green Performance Management.